Cardiac Resynchronization Therapy Acutely Improves Ventricular‐Arterial Coupling by Reducing the Arterial Load: Assessment by Pressure–Volume Loops. Issue 4 (28th January 2015) - PIERAGNOLI, PAOLO; PEREGO, GIOVANNI BATTISTA; RICCIARDI, GIUSEPPE; SACCHI, STEFANIA; PADELETTI, MARGHERITA; MICHELUCCI, ANTONIO; VALSECCHI, SERGIO; PADELETTI, LUIGI
<x xml:space="preserve">Abstract</x> Background Cardiac resynchronization therapy (CRT) has been demonstrated to improve ventricular‐arterial coupling by reducing effective arterial elastance (Ea) on long‐term follow‐up. Detailed invasive studies showing possible acute peripheral effects of CRT are not available. We evaluated the hemodynamic effects of CRT in patients with systolic dysfunction, in order to investigate the impact on ventricular‐arterial coupling and, in particular, on Ea immediately after the initiation of pacing. Methods We studied 37 heart failure patients undergoing CRT implantation based on conventional criteria. On implantation, left ventricular (LV) pressure and volume data were determined via a conductance catheter. Twelve patients with a standard indication for electrophysiologic study and preserved LV function served as a control group. Results In comparison with the control group, heart failure patients showed reduced systolic and diastolic function. LV end‐systolic elastance (Ees: end‐systolic pressure/volume) was impaired (0.79 ± 0.33 mm Hg/mL vs 1.84 ± 0.89 mm Hg/mL, P = 0.012) and Ees/Ea reduced (0.36 ± 0.17 vs 1.19 ± 1.81, P = 0.022). In heart failure patients, CRT immediately improved systolic function, increasing stroke work from 3.9 ± 1.8 L*mm Hg to 6.9 ± 3.3 L*mm Hg (P < 0.001) and Ees to 1.02 ± 0.62 mm Hg/mL (P = 0.001). Ea decreased from 2.59 ± 1.35 mm Hg/mL to 1.68 ± 0.91 mm Hg/mL (P < 0.001), leading to an increase in Ees/Ea to 0.70 ± 0.38 (P < 0.001). Conclusion Our data indicate that switching CRT on induces an immediate reduction in arterial load, conceivably as a consequence of restored autonomic balance.